Intrinsic properties of rat striatal output neurones and time-dependent facilitation of cortical inputs in vivo - Mahon, Séverine (Blackwell Science Inc, 2000)
1. In vivo intracellular recordings were performed from striatal output neurones (SONs) (n = 34) to test the role of their intrinsic membrane properties in the temporal integration of excitatory cortical synaptic inputs. 2. In a first series of experiments, intracellular injection of a test depolarising current pulse was preceded by a 200 ms suprathreshold prepulse, the two pulses having the same intensity. An increase in intrinsic excitability was observed as a decrease (55 ± 21 ms, n = 13) (mean ± s.d.) in latency to the first action potential of the test response compared to the prepulse response. This value decayed exponentially as a function of the time interval between the current pulses (τ= 364 ± 37 ms, n = 5). The voltage response of SONs was not modified by a prepulse that induced a membrane depolarisation < −62 mV. 3. The effect of the suprathreshold prepulse was tested on monosynaptic cortically evoked excitatory postsynaptic potentials (EPSPs). The ability to induce suprathreshold EPSPs was markedly increased by the prior depolarisation (n = 11 cells). This facilitation decayed progressively as a function of the time intervals between prepulses and cortical stimuli. The potentiation was not observed on small EPSPs reaching a peak potential < −65 mV (n = 3). 4. We conclude that SONs can optimise cortical information transfer by modifying their intrinsic excitability as a function of their past activation. It is likely that this time-dependent facilitation results, at least in part, from the kinetics of a striatal slowly inactivating potassium current available around −60 mV that recovers slowly from inactivation.